Adverse Childhood Experiences and Trauma-Informed Care: An Online Module for Pediatricians - Anna Schmitz (Association of American Medical Colleges, 2019)
Introduction The epidemic of adverse childhood experiences (ACEs) has many known health consequences. Robust research has linked ACEs to increased morbidity and mortality. Because of their frequent interaction with children and their families, pediatricians should be educated to recognize ACEs and practice trauma-informed care (TIC). There is a lack of education for pediatric residents on ACEs despite their significance. Our goals were to identify residents' baseline perceived importance, confidence, and frequency of discussion of ACEs, TIC, toxic stress, and resiliency and evaluate the efficacy of an educational module addressing these topics. Methods A 25-minute self-directed module was created for pediatric residents. The module was accessible online and independently completed by residents during the child advocacy rotation. Pre- and postmodule surveys using a 5-point Likert scale (1 = low, 5 = high) were administered, and median scores of 11 participants who completed both surveys were compared using the Wilcoxon signed rank test. Results Presurvey results demonstrated that residents were not confident discussing ACEs, TIC, or resiliency (median = 2). Residents reported that it was very important to discuss ACEs, toxic stress, and resiliency with families (median = 5), although they were rarely discussed in clinic (median = 1 or 2). Matched pre/post data showed significant increases in knowledge, confidence, and discussion frequency. Discussion The results demonstrated a need for ACE education for pediatric residents. The matched survey results showed the module's success in knowledge and behavior change. The module can be adapted to other learners to enhance understanding of ACEs.